Method for regulating and controlling dichroism of polyvinyl alcohol polarizing film

By adding reducing agent to the polyvinyl alcohol polarizing film and adjusting process parameters, the problem of polarizing film failure in high temperature environment is solved, the dichroism and optical properties of the film are improved, and more uniform iodine ion distribution and higher The polarization degree reduces the cost.

CN119177573APending Publication Date: 2024-12-24UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411367744.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The polyvinyl alcohol polarizing film fails in high temperature environments, resulting in poor polarization degree and polarization uniformity, affecting the performance of liquid crystal displays. The complexing ability of polyvinyl alcohol to iodine molecules is limited by the film's chemical structure and molecular chain characteristics.

Method used

Add reducing agents, such as sodium sulfite and potassium thiosulfate, to the polyvinyl alcohol polarizing film, to improve the distribution uniformity of iodine ions and the optical properties of the film by adjusting the process parameters during the dyeing and complementary coloring process. Specific steps include swelling, dyeing, crosslinking, stretching and complementing color, stretching and complementing color with a mixed solution of potassium iodide and boric acid, and pre-drying in a drying box.

Benefits of technology

By uniformly distributing iodine ions, the dichroism and optical performance of the polarizing film are improved, the polarization degree and uniformity of the polarizer are improved, the cost is reduced, and the toughness and processability of the film are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177573A_ABST
    Figure CN119177573A_ABST
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling the dichroism of a polyvinyl alcohol polarizing film, and belongs to the technical field of high polymer material processing.The method comprises the steps that a polyvinyl alcohol film is swelled by selecting proper steps and technological parameters; immersing the swelled polyvinyl alcohol film in iodine, potassium iodide and boric acid solutions for dyeing; immersing the dyed polyvinyl alcohol film into a boric acid solution for crosslinking; stretching the cross-linked polyvinyl alcohol film in a potassium iodide and boric acid solution; the stretched polyvinyl alcohol film is put into a color complementing bath for color complementing, and the dichroism of the high-gloss film is improved by adjusting the type of a reducing agent in the color complementing stage; and finally, drying the polyvinyl alcohol film after color complementing. The preparation method is simple, raw materials are easy to obtain, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material processing, and in particular relates to a method for regulating the dichroism of a polyvinyl alcohol polarizing film. Background Art

[0002] Polarizing film, one of the key components that determines the quality of liquid crystal displays, is prepared by swelling, dyeing, cross-linking, stretching, coloring, and drying polyvinyl alcohol optical films. Its key performance indicators - polarization degree and polarization uniformity - are affected by the iodine dyeing complexation efficiency of the polyvinyl alcohol film during the iodine dyeing and stretching process. Therefore, high-performance polarizers require polyvinyl alcohol polarizing films with adjustable dichroism. Improving the dichroism of polyvinyl alcohol polarizing films will help accelerate the localization process of polyvinyl alcohol polarizing films.

[0003] In the production process of polarizing film, the choice of polyvinyl alcohol base film has an important influence on the performance of the final product. When using the polyvinyl alcohol base film produced by Anhui Wanwei Group Co., Ltd. as the polarizing film, there are differences in the reaction equilibrium constant and reaction rate constant. , There are differences in the stability of polyiodide ions in the film. Polyvinyl alcohol-based films may have different hydroxyl density, branching content and crystallinity in chemical structure, which will affect the complexing ability of polyvinyl alcohol with iodine molecules. In addition, the interaction between polyvinyl alcohol and iodine molecules is also affected by the flexibility of the molecular chain and the strength of hydrogen bonds, which determine the stability of polyiodide ions and the optical properties of the film. Summary of the invention

[0004] The failure mechanism of polyvinyl alcohol polarizing film also shows significant differences under high temperature and high temperature and high humidity environments. The relative content is low because high temperature accelerates Towards dissociation, making Unstable and easy to decompose. In order to solve the above problems and improve the performance of polyvinyl alcohol polarizing film, the present invention proposes a method for regulating the dichroism of polyvinyl alcohol polarizing film, which is a method of adding a reducing agent to the polyvinyl alcohol polarizing film, so that the iodine ions are more evenly distributed in the polyvinyl alcohol film to improve the polarization performance of the polarizer. Based on the above understanding, the purpose of the present invention is to improve the optical performance of the polarizer by improving the dichroism of the polarizing film itself.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: A method for controlling the dichroism of a polyvinyl alcohol polarizing film comprises the following steps: Step S1, immersing the polyvinyl alcohol film in water for swelling, the swelling temperature is 20-35° C., and the time is 100-200 seconds; Step S2, immersing the swollen polyvinyl alcohol film in a dyeing solution for dyeing at a temperature of 25-35° C. for 50-300 seconds, wherein the dyeing solution is a mixed solution of iodine and potassium iodide, wherein the mass percentage content of iodine is 0.5-1%, and the mass percentage content of potassium iodide is 10-20%; Step S3, immersing the polyvinyl alcohol film in a boric acid solution to cross-link the dyed polyvinyl alcohol film, the cross-linking temperature is 30-50° C., the mass percentage of boric acid in the boric acid solution is 3-5%, and the time is 50-100 seconds; Step S4, immersing the polyvinyl alcohol film in a mixed solution of potassium iodide and boric acid, and stretching the polyvinyl alcohol film at a stretching temperature of 40-60° C.; in the mixed solution of potassium iodide and boric acid, the mass percentage content of potassium iodide is 1-4%, the mass percentage content of boric acid is 2-5%, and the stretching ratio is 1.0-1.5 times; Step S5, immersing the stretched polyvinyl alcohol film in a mixed solution of potassium iodide, boric acid and a reducing agent (the reducing agent is sodium sulfite and / or potassium thiosulfate) for color correction; in the mixed solution of potassium iodide, boric acid and a reducing agent, the mass percentage of potassium iodide is 3-3.5%, the mass percentage of boric acid is 0.5-1%, the mass percentage of the reducing agent is 2-5%, the temperature for color correction is 20-40°C, and the time for color correction is 10-20s; Step S6, pre-drying the color-corrected polyvinyl alcohol film in a drying oven, with the drying time being 50-200 seconds.

[0006] Further, in step S1, the polyvinyl alcohol film is immersed in water for swelling, the swelling temperature is 20-35°C, and the time is 100-200 seconds; for example, the swelling temperature is 20°C, 25°C, 30°C or 35°C, and the time is 100 seconds, 125 seconds, 150 seconds, 175 seconds or 200 seconds.

[0007] Further, in step S2, the swollen polyvinyl alcohol film is immersed in a dyeing solution for dyeing, the dyeing temperature is 25°C, 30°C or 35°C, and the time is 50 seconds, 100 seconds, 125 seconds, 150 seconds, 175 seconds, 200 seconds or 300 seconds. The dyeing solution is a mixed solution of iodine and potassium iodide, in which the mass percentage content of iodine is 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, and the mass percentage content of potassium iodide is 10%, 12%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0008] Furthermore, in step S3, the polyvinyl alcohol film is immersed in a boric acid solution to cross-link the dyed polyvinyl alcohol film. The cross-linking temperature is 30°C, 35°C, 40°C, 45°C or 50°C. In the boric acid solution, the mass percentage of boric acid is 3%, 3.5%, 4%, 4.5% or 5%, and the time is 50 seconds, 70 seconds, 90 seconds or 100 seconds.

[0009] Furthermore, in step S4, the polyvinyl alcohol film is immersed in a mixed solution of potassium iodide and boric acid, and the polyvinyl alcohol film is stretched at a stretching temperature of 40°C, 45°C, 50°C or 60°C; in the mixed solution of potassium iodide and boric acid, the mass percentage content of potassium iodide is 1%, 1.5, 2%, 3%, 3.5% or 4%, the mass percentage content of boric acid is 2%, 3%, 3.5%, 4%, 4.5% or 5%, and the stretching ratio is 1.0 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times or 1.5 times.

[0010] Furthermore, in step S5, the stretched polyvinyl alcohol film is immersed in a mixed solution of potassium iodide, boric acid and a reducing agent (sodium sulfite, potassium thiosulfate) for color correction; in the mixed solution of potassium iodide, boric acid and a reducing agent, the mass percentage of potassium iodide is 3%, 3.1%, 3.2%, 3.3%, 3.4% or 3.5%, the mass percentage of the reducing agent is 2%, 3%, 3.5%, 4%, 4.5% or 5%, the temperature for color correction is 20°C, 25°C, 30°C, 35°C or 40°C, and the color correction time is 10s, 12s, 15s or 20s.

[0011] Furthermore, in step S6, the color-complemented polyvinyl alcohol film is pre-dried in a drying oven, and the drying time is 50 seconds, 70 seconds, 90 seconds, 100 seconds, 150 seconds or 200 seconds.

[0012] Advantages and positive effects: According to the technical scheme of the present invention, by selecting appropriate steps and process parameters, the polyvinyl alcohol film is first swollen; the swollen polyvinyl alcohol film is immersed in an iodine, potassium iodide and boric acid solution for dyeing; the dyed polyvinyl alcohol film is then immersed in a boric acid solution for cross-linking; the cross-linked polyvinyl alcohol film is then stretched in a potassium iodide and boric acid solution; the stretched polyvinyl alcohol film is then placed in a color-replenishing bath for color-replenishing, and the dichroism of the high-light film is improved by adjusting the type of reducing agent in the color-replenishing stage; and finally the color-replenishing polyvinyl alcohol film is dried. The preparation method is simple, and the raw material cost is easy to obtain and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the overall processing flow chart of polyvinyl alcohol polarizing film.

[0014] Figure 2These are UV-visible spectrophotometer graphs of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with added sodium sulfite), and polyvinyl alcohol polarizing film (with added potassium thiosulfate).

[0015] Figure 3 (a) is the Raman spectra of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with added sodium sulfite), and polyvinyl alcohol polarizing film (with added potassium thiosulfate), and (b) is the ratio of the relative content of iodine triion and iodine pentaion.

[0016] Figure 4 (a) is the wide-angle diffraction one-dimensional integral curve of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with added sodium sulfite), and polyvinyl alcohol polarizing film (with added potassium thiosulfate), and (b) is a crystallinity comparison diagram.

[0017] Figure 5 These are the low-field nuclear magnetic resonance free decay curves of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with sodium sulfite added), and polyvinyl alcohol polarizing film (with potassium thiosulfate added). DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution: like Figure 1 As shown, the overall processing flow of the polyvinyl alcohol polarizing film includes the following steps: Step S1, preparing a polyvinyl alcohol-based film, immersing the polyvinyl alcohol-based film in water for swelling, the swelling temperature is 20-35° C., and the time is 100-200 seconds; Step S2, immersing the swollen polyvinyl alcohol film in a dyeing solution for dyeing, the dyeing temperature is 25-35° C., the time is 50-300 seconds, the dyeing solution is a mixed solution of iodine and potassium iodide, and the mass percentage content of iodine in the mixed solution is 0.5-1%, and the mass percentage content of potassium iodide is 10-20%; Step S3, immersing the polyvinyl alcohol film treated in step S2 into a boric acid solution to crosslink the dyed polyvinyl alcohol film, the crosslinking temperature is 30-50° C., the mass percentage of boric acid in the boric acid solution is 3-5%, and the crosslinking time is 50-100 seconds; Step S4, immersing the polyvinyl alcohol film treated in step S3 in a mixed solution of potassium iodide and boric acid, and stretching the polyvinyl alcohol film at a stretching temperature of 40-60° C.; in the mixed solution of potassium iodide and boric acid, the mass percentage content of potassium iodide is 1-4%, the mass percentage content of boric acid is 2-5%, and the stretching ratio is 1.0-1.5 times; Step S5, immersing the polyvinyl alcohol film stretched in step S4 in a mixed solution of potassium iodide, boric acid and a reducing agent for color correction; in the mixed solution of potassium iodide, boric acid and a reducing agent, the mass percentage of potassium iodide is 3-3.5%, the mass percentage of the reducing agent is 2-5%, the color correction temperature is 20-40°C, and the color correction time is 10-20s; Step S6, pre-drying the color-corrected polyvinyl alcohol film in a drying oven, with the drying time being 50-200 seconds.

[0019] Example 1 909 g of polyvinyl alcohol (PVA) (degree of polymerization 2400, degree of alcoholysis greater than 99%, weight average molecular weight M w About 75kg·mo1 -1, the dispersion degree is 1.8, the same as in the following examples) raw materials and 90.9g glycerol, 1g sodium dodecylbenzene sulfonate surfactant, dissolved in 4000g deionized water under 150℃ sealing condition, to prepare PVA casting solution, the dissolution reaction time is 10h. The formed casting solution is extruded from the die after degassing and filtering by the extruder, and after being dried by the casting roller at 90℃ for 1min, it enters 11 groups of drying rollers (temperature in the range of 40-100℃) to repeatedly dry the front and back sides of the film for 2min, and then enters the air flotation oven for heat treatment (110℃) for 1min to fix the shape, and finally rolled up to obtain the PVA optical film (i.e., polyvinyl alcohol-based film), the film thickness of which is 30μm. A polyvinyl alcohol-based film with a thickness of 30 μm was immersed in water for swelling in the water at a swelling temperature of 30°C for 150 seconds; the swollen polyvinyl alcohol film was immersed in a dyeing solution for dyeing, the dyeing solution was an aqueous solution of iodine and potassium iodide, the mass percentage of iodine in the aqueous solution of iodine and potassium iodide was 0.5%, the mass percentage of potassium iodide was 15%, the dyeing temperature was 30°C, and the dyeing time was 200 seconds; the polyvinyl alcohol film was immersed in a boric acid solution to crosslink the dyed polyvinyl alcohol film, the mass percentage of boric acid in the boric acid solution was 3%, the crosslinking temperature was 38°C, and the time was 80 seconds; the polyvinyl alcohol film was immersed in a mixture of potassium iodide and boric acid to crosslink the dyed polyvinyl alcohol film. The method comprises the following steps: stretching a polyvinyl alcohol film at a stretching temperature of 50°C in a solution, wherein the mass percentage of potassium iodide in the mixed solution of potassium iodide and boric acid is 3%, the mass percentage of boric acid is 2%, and the stretching ratio is 1.5 times; immersing the stretched polyvinyl alcohol film in a mixed solution of potassium iodide, boric acid and sodium sulfite for color correction, and the color correction time is 15s. In the mixed solution, the mass percentage of potassium iodide is 3.5%, the mass percentage of boric acid is 0.5%, the mass percentage of sodium sulfite is 4%, and the color correction temperature is 28°C; and pre-drying the polyvinyl alcohol film after color correction in a drying oven, and the drying temperature is 50°C and the drying time is 150s.

[0020] Example 2 909g of PVA raw material, 90.9g of glycerol and 1g of sodium dodecylbenzene sulfonate surfactant were dissolved in 4000g of deionized water at 150°C in a sealed state to prepare PVA casting solution, and the dissolution reaction time was 10h. The formed casting solution was degassed and filtered by an extruder and then extruded from a die. After being dried by a casting roller at 90°C for 1min, it entered 11 sets of drying rollers (temperature in the range of 40-100°C) to repeatedly dry the front and back sides of the film for 2min, and then entered an air flotation oven for heat treatment (110°C) for 1min to finalize, and finally rolled up to obtain a PVA optical film (i.e., a polyvinyl alcohol-based film) with a film thickness of 30μm. A polyvinyl alcohol-based film with a thickness of 30 μm is immersed in water for swelling in the water at a swelling temperature of 30°C for 150 seconds; the swollen polyvinyl alcohol film is immersed in a dyeing solution for dyeing, the dyeing solution is an aqueous solution of iodine and potassium iodide, the mass percentage content of iodine in the aqueous solution of iodine and potassium iodide is 0.5%, the mass percentage content of potassium iodide is 15%, the dyeing temperature is 30°C, and the time is 200 seconds; the polyvinyl alcohol film is immersed in a boric acid solution to crosslink the dyed polyvinyl alcohol film, the mass percentage of boric acid in the boric acid solution is 3%, the crosslinking temperature is 38°C, and the time is 80 seconds; the polyvinyl alcohol film is immersed in a mixed solution of potassium iodide and boric acid The polyvinyl alcohol film is stretched at a stretching temperature of 50°C, wherein the mass percentage of potassium iodide in the mixed solution of potassium iodide and boric acid is 3%, the mass percentage of boric acid is 2%, and the stretching ratio is 1.5 times; the stretched polyvinyl alcohol film is immersed in a mixed solution of potassium iodide, boric acid and potassium thiosulfate for color correction, and the color correction time is 15s, wherein the mass percentage of potassium iodide in the mixed solution is 3.5%, the mass percentage of boric acid is 0.5%, the mass percentage of potassium thiosulfate is 4%, and the color correction temperature is 28°C; the polyvinyl alcohol film after color correction is pre-dried in a drying oven, and the drying temperature is 50°C and the drying time is 150s.

[0021] Comparative Example 1 909g of PVA raw material, 90.9g of glycerol and 1g of sodium dodecylbenzene sulfonate surfactant were dissolved in 4000g of deionized water at 150°C in a sealed state to prepare PVA casting solution, and the dissolution reaction time was 10h. The formed casting solution was degassed and filtered by an extruder and then extruded from a die. After being dried by a casting roller at 90°C for 1min, it entered 11 sets of drying rollers (temperature in the range of 40-100°C) to repeatedly dry the front and back sides of the film for 2min, and then entered an air flotation oven for heat treatment (110°C) for 1min to finalize, and finally rolled up to obtain a PVA optical film (i.e., a polyvinyl alcohol-based film) with a film thickness of 30μm. A polyvinyl alcohol-based film with a thickness of 30 μm is immersed in water for swelling in the water at a swelling temperature of 30°C for 150 seconds; the swollen polyvinyl alcohol film is immersed in a dyeing solution for dyeing, the dyeing solution is an aqueous solution of iodine and potassium iodide, the mass percentage content of iodine in the aqueous solution of iodine and potassium iodide is 0.5%, the mass percentage content of potassium iodide is 15%, the dyeing temperature is 30°C, and the time is 200 seconds; the polyvinyl alcohol film is immersed in a boric acid solution to crosslink the dyed polyvinyl alcohol film, the mass percentage of boric acid in the boric acid solution is 3%, the crosslinking temperature is 38°C, and the time is 80 seconds; the polyvinyl alcohol film is immersed in potassium iodide The method comprises the following steps: stretching a polyvinyl alcohol film in a mixed solution of potassium iodide and boric acid at a stretching temperature of 50°C, wherein the mass percentage of potassium iodide in the mixed solution of potassium iodide and boric acid is 3%, the mass percentage of boric acid is 2%, and the stretching ratio is 1.5 times; immersing the stretched polyvinyl alcohol film in a mixed solution of potassium iodide and boric acid for color correction, and the color correction time is 15s, wherein the mass percentage of potassium iodide in the mixed solution of potassium iodide and boric acid is 3.5%, the mass percentage of boric acid is 0.5%, and the color correction temperature is 28°C; pre-drying the polyvinyl alcohol film after color correction in a drying oven, and the drying temperature is 50°C and the drying time is 150s.

[0022] The PVA polarizing films prepared in the above examples and comparative examples were tested by UV-visible spectrophotometer to obtain the absorbance of the polarizing films. The results are as follows: Figure 2 As shown in the figure, after adding reducing agents (sodium sulfite, potassium thiosulfate), the absorbance is improved to a certain extent compared with the original polarizing film.

[0023] The PVA polarizing films prepared in the above examples and comparative examples were tested by Raman spectroscopy to obtain the iodine ion distribution intensity diagram of the polarizing film. The results are as follows: Figure 3 As shown, Figure 3(a) is the Raman spectra of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with sodium sulfite added), and polyvinyl alcohol polarizing film (with potassium thiosulfate added), and (b) is the ratio of the relative content of iodine triion and iodine pentaion. Compared with the original polarizing film, more iodine pentaions are reduced to iodine triions when reducing agents (sodium sulfite and potassium thiosulfate) are added, solving the problem of uniform distribution from the perspective of optical performance.

[0024] The PVA polarizing films prepared in the above examples and comparative examples were subjected to wide-angle diffraction tests to obtain a one-dimensional integral curve of the polarizing film. The results are as follows: Figure 4 As shown, Figure 4 (a) is a one-dimensional integral curve of wide-angle diffraction of polyvinyl alcohol polarizing film, polyvinyl alcohol polarizing film (with sodium sulfite added), and polyvinyl alcohol polarizing film (with potassium thiosulfate added), and (b) is a crystallinity comparison diagram. After adding reducing agents (sodium sulfite and potassium thiosulfate) and comparing with the original polarizing film, different crystallinities were obtained according to the crystal plane information after fitting the three curves, showing that the toughness of the polarizing film is further improved after adding reducing agents.

[0025] The PVA polarizing films prepared in the above examples and comparative examples were subjected to wide-angle diffraction tests to obtain the low-field nuclear magnetic resonance free decay curves of the polarizing films. The results are as follows: Figure 5 As shown, Figure 5 The low-field nuclear magnetic resonance free decay curves of polyvinyl alcohol polarized film, polyvinyl alcohol polarized film (with sodium sulfite added), and polyvinyl alcohol polarized film (with potassium thiosulfate added) are shown in Figure 1. Compared with the original polarized film, the rigid part decays longer after adding the reducing agent (sodium sulfite and potassium thiosulfate), indicating that the proportion of the rigid component decreases, indicating that the processability of the polarized film is improved after adding the reducing agent.

Claims

1. A method for controlling the dichroism of a polyvinyl alcohol polarizing film, characterized in that: The following steps are involved: Step S1, immersing the polyvinyl alcohol film in water for swelling, the swelling temperature is 20-35° C., and the time is 100-200 seconds; Step S2, immersing the swollen polyvinyl alcohol film in a dyeing solution for dyeing, the dyeing temperature is 25-35° C., the time is 50-300 seconds, the dyeing solution is a mixed solution of iodine and potassium iodide, and the mass percentage content of iodine in the mixed solution of iodine and potassium iodide is 0.5-1%, and the mass percentage content of potassium iodide is 10-20%; Step S3, immersing the polyvinyl alcohol film in a boric acid solution to cross-link the dyed polyvinyl alcohol film, the cross-linking temperature is 30-50° C., the mass percentage of boric acid in the boric acid solution is 3-5%, and the cross-linking time is 50-100 seconds; Step S4, immersing the polyvinyl alcohol film in a mixed solution of potassium iodide and boric acid, and stretching the polyvinyl alcohol film at a stretching temperature of 40-60° C.; in the mixed solution of potassium iodide and boric acid, the mass percentage content of potassium iodide is 1-4%, the mass percentage content of boric acid is 2-5%, and the stretching ratio is 1.0-1.5 times; Step S5, immersing the stretched polyvinyl alcohol film in a mixed solution of potassium iodide, boric acid and a reducing agent for color correction; in the mixed solution of potassium iodide, boric acid and a reducing agent, the mass percentage of potassium iodide is 3-3.5%, the mass percentage of boric acid is 0.5-1%, the mass percentage of the reducing agent is 2-5%, the temperature of color correction is 20-40°C, and the color correction time is 10-20s; Step S6, pre-drying the color-corrected polyvinyl alcohol film in a drying oven, with the drying time being 50-200 seconds.

2. The method according to claim 1, characterized in that In step S1, the specific method of swelling includes: immersing the polyvinyl alcohol film in water for swelling, the swelling temperature is 25-35°C, and the time is 100-200 seconds.

3. The method according to claim 1, characterized in that In step S2, the specific steps of dyeing include: dyeing temperature is 30-35°C, time is 200-300 seconds, the mass percentage content of iodine is 0.5-0.8%, and the mass percentage content of potassium iodide is 15-20%.

4. The method according to claim 1, characterized in that: In step S3, the specific steps of cross-linking include: the cross-linking temperature is 38-50° C., the mass percentage of boric acid in the boric acid solution is 3-4%, and the cross-linking time is 80-100 seconds.

5. The method according to claim 1, characterized in that In step S4, the specific steps of stretching include: the stretching temperature is 50-60°C; in the mixed solution of potassium iodide and boric acid, the mass percentage content of potassium iodide is 3-4%, the mass percentage content of boric acid is 2-4%, and the stretching ratio is 1.1-1.5 times.

6. The method according to claim 1, characterized in that In step S5, the reducing agent is sodium sulfite and / or potassium thiosulfate.

7. The method according to claim 1, characterized in that In step S6, the drying temperature is 50-60°C.

Citation Information

Cited By

  • An antistatic waterproof composite film for a polarizing plate and a process for preparing the same

    CN122685940A